ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL, TINGKAT HUNIAN HOTEL DAN JUMLAH WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA BATU - Ima Rahmalia; Riko Setya Wijaya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), Hotel Occupancy Rate (HOR), and the Number of Tourists on the Local Own-Source Revenue (PAD) of Batu City during the 2015–2024 period. This study employed a quantitative approach using secondary time-series data obtained from the Central Bureau of Statistics (BPS) of Batu City, the Central Bureau of Statistics of East Java Province, and the Directorate General of Fiscal Balance (DJPK). The data were analyzed using multiple linear regression with the assistance of SPSS version 17 and were preceded by classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results indicate that Gross Regional Domestic Product and the Number of Tourists have a positive and significant effect on the Local Own-Source Revenue of Batu City, whereas the Hotel Occupancy Rate has no significant effect on Local Own-Source Revenue. Simultaneously, Gross Regional Domestic Product, Hotel Occupancy Rate, and the Number of Tourists significantly affect the Local Own-Source Revenue of Batu City. These findings suggest that regional economic growth and increasing tourist arrivals play an important role in strengthening local fiscal capacity. Therefore, the Batu City Government is expected to continue optimizing the tourism sector and promoting regional economic growth to sustainably increase Local Own-Source Revenue.